Analysis of proteome adaptation reveals a key role of the bacterial envelope in starvation survival. Issue 12 (7th December 2022) - Schink, Severin; Ammar, Constantin; Chang, Yu‐Fang; Zimmer, Ralf; Basan, Markus
Abstract: Bacteria reorganize their physiology upon entry to stationary phase. What part of this reorganization improves starvation survival is a difficult question because the change in physiology includes a global reorganization of the proteome, envelope, and metabolism of the cell. In this work, we used several trade‐offs between fast growth and long survival to statistically score over 2, 000 Escherichia coli proteins for their global correlation with death rate. The combined ranking allowed us to narrow down the set of proteins that positively correlate with survival and validate the causal role of a subset of proteins. Remarkably, we found that important survival genes are related to the cell envelope, i.e., periplasm and outer membrane, because the maintenance of envelope integrity of E. coli plays a crucial role during starvation. Our results uncover a new protective feature of the outer membrane that adds to the growing evidence that the outer membrane is not only a barrier that prevents abiotic substances from reaching the cytoplasm but also essential for bacterial proliferation and survival. Synopsis: Proteomic analysis of Escherichia coli under various growth conditions reveals that a trade‐off between growth and starvation can be explained by bacteria investing resources into the cell envelope to reduce its permeability, which improves their lifespan at the expense of growth. A trade‐off between growth rate and death rate confines the fitness of bacteria across environments. Analysis of proteome signatures across five independent perturbations reveals the cell envelope as a key determinant of the death rate. The trade‐off can be abolished by changing the environment to a low salt but osmo‐balanced medium where cell envelope integrity is not limiting. Abstract : Proteomic analysis of Escherichia coli under various growth conditions reveals that a trade‐off between growth and starvation can be explained by bacteria investing resources into the cell envelope to reduce its permeability, which improves their lifespan at the expense of growth.